2020
DOI: 10.1038/s41419-020-2279-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Schnurri-3 regulates BMP9-induced osteogenic differentiation and angiogenesis of human amniotic mesenchymal stem cells through Runx2 and VEGF

Abstract: Human amniotic mesenchymal stem cells (hAMSCs) are multiple potent progenitor cells (MPCs) that can differentiate into different lineages (osteogenic, chondrogenic, and adipogenic cells) and have a favorable capacity for angiogenesis. Schnurri-3 (Shn3) is a large zinc finger protein related to Drosophila Shn, which is a critical mediator of postnatal bone formation. Bone morphogenetic protein 9 (BMP9), one of the most potent osteogenic BMPs, can strongly upregulate various osteogenesis-and angiogenesis-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…At the same time, we identified that Notch1 signaling potentiated BMP9-induced osteogenic differentiation of MSCs by potentiating the osteogenesis-angiogenesis coupling [16]. In addition, we clarified that Schnurri-3 simultaneously regulates BMP9-induced osteogenic differentiation and blood vessel formation in human amniotic MSCs [31]. The research indicated that angiogenic signaling participated in BMP9-induced bone formation of MSCs.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…At the same time, we identified that Notch1 signaling potentiated BMP9-induced osteogenic differentiation of MSCs by potentiating the osteogenesis-angiogenesis coupling [16]. In addition, we clarified that Schnurri-3 simultaneously regulates BMP9-induced osteogenic differentiation and blood vessel formation in human amniotic MSCs [31]. The research indicated that angiogenic signaling participated in BMP9-induced bone formation of MSCs.…”
Section: Introductionmentioning
confidence: 78%
“…Meanwhile, BMP9 was proved to regulate postnatal angiogenesis, which indicated the angiogenic differentiation potential of BMP9 [45,46]. In previous studies, we have identified that angiogenic signaling is essential for BMP9-mediated osteogenic differentiation of MSCs [16,30,31], however, BMP9-induced angiogenic differentiation of MSCs and the relationship between BMP9-mediated osteogenic and angiogenic differentiation of MSCs were not well established. In the present study, we found that BMP9 exhibited dual roles in inducing MSCs osteogenic and angiogenic differentiation in vitro, and further in vivo assays confirmed that BMP9-mediated bone formation are coupled with angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…1D) The hSMSCs express most of the MSCs markers and capable of multidirectional differentiation potential According to the criteria for mesenchymal stem cell identi cation,we identify the surface marker of hSMSCs using ow cytometry. [29,32] Flow cytometric results showed that P1 hSMSCs were positive for MSC markers CD73, CD90, and CD105 and weakly expressed hematopoietic markers CD34, CD14, CD45, which indicated that P1 hSMSCs express most of the consensus MSC markers, suggesting that these cells may possess MSC-like characteristics. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, to identify the multiple differentiation potential [32,33], cells were seeded in a 6-well plate, and the differentiation medium was replaced when the cell density reached 60%. Osteogenic medium was composed of DMEM with 10% FBS, 10 mM bglycerophosphate (Sigma-Aldrich), 50 mg/mL ascorbate (Sigma-Aldrich), and 100 nM dexamethasone (Sigma-Aldrich).…”
Section: Phenotypic Identification Of Hsmscsmentioning
confidence: 99%